The Effects of Acute Exercise on Retroactive Memory Interference. Issue 1 (January 2020) - Loprinzi, Paul D.; Frith, Emily; Crawford, Lindsay
Purpose: Retroactive interference involves the disruption of previously encoded information from newly learned information and thus may impair the consolidation of long-term memory. The objective of this study was to evaluate whether acute exercise can attenuate retroactive memory interference. Design: Three experimental studies were employed. Experiment 1 employed a between-subject randomized control trial (RCT) involving moderate-intensity walking (15 minutes). Experiment 2 employed a between-subject RCT involving high-intensity jogging (15 minutes). Experiment 3 employed a within-subject RCT involving moderate-intensity walking (15 minutes). Setting: University setting. Participants: One hundred twelve young adults. Measures: After exercise, memory interference was evaluated from an episodic word-list memory task, involving the recall of 2 word lists. Results: The pooled effect size (standard difference in means: −0.35; 95% confidence interval: −0.64 to −0.06) across the 3 experiments was statistically significant ( P = .01). Conclusion: We provide suggestive evidence that acute, short-duration exercise may help attenuate a retroactive memory interference effect. Implications of these findings for exercise to improve memory and attenuate memory decay are discussed.